Practicum in fish and salt farming conducted at Parañaque, Metro Manila. - Oller, Fe S. (Miagao, Iloilo College of Fisheries, 1979)
One of the objectives of the government today is the development of our natural resources with emphasis placed on fish production. The University of the Philippines, College of fisheries aims to help maximize fish production by training students to the scientific application of fishpond management. This is the very reason why fish 197 (practicum) is a required course/ partial fulfilment for graduation. It serves as a training ground whereby the students put unto practice things that they have learned theoretically in school. In this manner, they acquire technical knowledge and experience of aquacultural practices, including the important aspects in proper management for better production of fish. They develop the ability to formulate suggestions and recommendations to increase production. Our work entitled "practicum in fish and salt farming conducted at Paranague, Matro Manila, is simplya rsume of the activities that we have conducted during the second semester of the School-Year 1978-1979(November-April). It was a five-month training at Gurrero fishpond in Paranague and all the saltbeds lined along with Imelda Avenue, Paranague where we made scientific analysis, frequent observations and a series of interview with the purpose of widening our knowledge. The training enabled us to acquire some practical formations on the actual management and various industrial practices in fishpond-salt farm operations.
Keywords: Fish-Culture.